Work function-tailored graphene via transition metal encapsulation as a highly active and durable catalyst for the oxygen reduction reaction. Issue 7 (5th April 2019) - Sharma, Monika; Jang, Jue-Hyuk; Shin, Dong Yun; Kwon, Jeong An; Lim, Dong-Hee; Choi, Daeil; Sung, Hukwang; Jang, Jeonghee; Lee, Sang-Young; Lee, Kwan Young; Park, Hee-Young; Jung, Namgee; et al.
Abstract : A novel design concept of a three-dimensional graphene shell encapsulated cobalt nanostructure as a new route to tune the work function of graphene for enhanced ORR. Abstract : To dramatically improve the performance of non-precious catalyst-based anion exchange membrane fuel cells (AEMFCs), a conceptual change in the structure of conventional electrocatalysts is needed. Here we report a novel work function tailoring of graphene via adopting a graphene shell-encapsulated Co nanoarchitecture to efficiently activate the graphitic carbon shell as an exclusive and main active site for the oxygen reduction reaction (ORR). Theoretical calculations and electrochemical analysis suggest that the charge transfer from core Co nanoparticles to the outer graphene shell results in a significant change in the electronic structure of the graphene shell and reduces its work function. The present catalyst shows high ORR catalytic activity but exceptionally enhanced durability compared to a Pt catalyst in alkaline media, which is attributed mainly to the reduced work function of the outer graphene shell and the 3D nanographene structure providing a large number of active carbon sites. The single cell using the graphene shell-encapsulated Co nanoparticles as a cathode catalyst produces a high maximum power density of 412 mW cm −2, making this among the best non-precious catalysts for the ORR reported so far. Therefore, our results demonstrate a promising strategy to rationally design inexpensive and durable oxygen reduction catalysts, and this hybrid concept will provide a new perspective for catalyst structures which can practically be used in AEMFCs.